Ferrocement composites for strengthening of concrete columns: A review. (30th January 2018) - Kaish, A.B.M.A.; Jamil, M.; Raman, S.N.; Zain, M.F.M.; Nahar, Lutfun
Highlights: Behaviour of ferrocement jacketed concrete columns are reviewed and discussed. Confinement mechanism and models for ferrocement confined column are also reviewed. Research gaps are identified and suggestions for further development are proposed. Abstract: The retrofitting and strengthening of concrete structures are becoming integral parts in construction and structural engineering practices owing to various situations that necessitate the enhancement in the capacity of structural members. Ferrocement composites are widely used for structural strengthening and rehabilitation in developing countries. The uniform distribution and high surface area-to-volume ratio of the reinforcement (wire mesh) of such composites improve the crack-arresting mechanism. Given these properties, ferrocement is an ideal material for repairing and strengthening old and deteriorated structures or structural members. Ferrocement composite has also been used as a jacketing material to strengthen axially loaded reinforced concrete (RC) members. Strengthening of concrete structures is an essential part of construction activities at present because these structures often suffer damage as a result of numerous environmental factors. The significance of these activities also increases with the insufficient capacity of structures that have been designed using old design codes. However, no codes have been developed for ferrocement composites as jacketing material to date. Moreover, a well-defined method for confining RC columns using ferrocement has not been established because of the lack of adequate research in this field. Thus, this study aggregates the current state of knowledge by reviewing available literature on the ferrocement jacketing of concrete columns and on ferrocement confinement effects. This study also determines research gaps in this field and suggests directions for future research to establish ferrocement composites as a feasible material for strengthening axially loaded concrete members.